Identification of Educational Governance Problems in Rural Areas as a Basis for Policy Recommendations - Tulus Joseph Herianto; Nicholas Marpaung (Talenta Publisher, 2026)
Educational governance in rural areas involves complex challenges because educational quality is shaped not only by classroom instruction but also by teacher availability, infrastructure, digital access, financing capacity, community participation, and geographical conditions. This study aims to identify major educational governance problems in rural areas and formulate policy directions through a synthesis of empirical research and contemporary issues reported in news sources. A qualitative approach using qualitative document analysis was employed. The data consisted of peer-reviewed journal articles and news or institutional news publications addressing educational provision in rural and remote settings. The documents were analysed using reflexive thematic analysis through data familiarisation, coding, theme development, theme review, theme definition, and interpretation. Six major themes emerged: (1) teacher distribution and workforce sustainability; (2) infrastructure limitations and the digital divide; (3) misalignment between uniform policies and local needs; (4) limited community participation and educational accountability; (5) funding constraints and resource mobilisation; and (6) the vulnerability of educational services to geographical conditions and external disruptions. The findings indicate that rural educational problems cannot be adequately addressed through isolated interventions. This study proposes the 6P Framework for Rural Educational Governance—Mapping, Personnel, Infrastructure, Participation, Financing, and Protection—as a conceptual basis for developing more context-sensitive educational policies. Rural education policy should move beyond uniform approaches toward needs-based, collaborative, and resilient governance.